Race and police killings: examining the links between racial threat and police shootings of Black Americans - Gray, Caroline (Journal of ethnicity in criminal justice, 2020)
This study empirically examines recent race-specific police shootings and offers a theoretical test of racial threat arguments. Our analysis includes all aspects of threat – economic, political, and racial composition – when examining state-level counts of police shootings of Black citizens spanning 2014–2016. For comparison, police shootings of Whites were also analyzed. Significant findings for racial composition are reported across both races, while political predictors are significant in the Black-specific model when controlling for other structural features. Our results also highlight the need to disaggregate police shootings by race. With partial support for racial threat arguments, we offer directions for future research.